(untitled) (Fiep Bulletin - online, 2013)
Food is central to the maintenance of body health, and is directly related to the physiological and psychological functions of athletes and non athletes. Aim: To assess the nutritional knowledge of bodybuilders of Anápolis city. Methods: Participants were 60 bodybuilders aged 30.58 ± 8.6 years, 55% women. Three questionnaires were used to collect data, which assessed students’ knowledge about nutrition, diet and use of supplements. Results: It was shown that much of the sample did not know the functions of macronutrients as well as their caloric value. What happens also as micronutrients. The majority of the sample means having a greater number of meals is the best choice, which goes against the scientific evidence. Evidenced an excessive intake protein, probably due to the lack of proper professional guidance. We highlight an indiscriminate use of supplements of various kinds. Conclusion: The bodybuilders possess reasonable knowledge regarding nutrition, leaving the desired especially in relation to the establishment of nutrient sources, as well as correct distribution of macro nutrients, showing that some practices such as excessive consumption of protein also are regarded as healthy and ideal. The present study confirms the data found in the literature on nutritional supplementation: observed relative percentage of people who reported using nutritional supplements (36.7%), and among the most popular products we highlight the products composed of proteins and amino acids.